Compact ATR-WGS-Integrated Bioethanol Fuel Processor for Portable and On-board Fuel Cell Applications - Kim, Yongmin; Kwak, Yeonsu; Lee, Yu-Jin; Jo, Young Suk; Sohn, Hyuntae; Jeong, Hyangsoo; Kim, Hyoung-Juhn; Han, Jong Hee; Nam, Suk Woo; Yoon, Chang Won (American Chemical Society, 2020)
A compact bioethanol fuel processor with an all-in-one design of the auto-thermal reforming (ATR) and water-gas-shift (WGS) reactors was developed. The fuel processor has unique features, such as the annular-type reactors which are constructed by stacking disk-shaped Rh/Gd-doped-ceria-coated structured catalysts and insertion of an internal heat exchanger between the two reactors. This integration renders two distinctive temperature zones for the ATR and WGS reactions in the fuel processor with a total volume of 135 cm(3). A hydrogen production rate of 30 sccm H-2/mL(reactor) equivalent to ca. 2.3 kW(e)/L-reactor, and a CO level of 2.4-2.7 mol % (dry basis) were achieved under continuous long-term operation for 700 h. The as-produced gas is ready-to-use in high-temperature polymer electrolyte membrane fuel cells, and this combination can be a competitive solution for hydrogen mobility requiring high energy storage density.
Keywords: WATER-GAS-SHIFT; HYDROGEN-PRODUCTION; PARTIAL OXIDATION; BIO-ETHANOL; RHODIUM CATALYSTS; PRODUCE HYDROGEN; EXHAUST HEAT; NOBLE-METALS; RH; REACTOR